Union Democracy and the Law in Canada - Lynk, Michael (Just Labour, 2002)
The legal approach in Canada towards the regulation of trade union democracy has sought to balance individual member’s rights with respect for the autonomy of unions. While the United States and England have heavily legislated the areas of internal trade union affairs, Canada has enacted relatively few laws in this area. Rather, unions in Canada have enjoyed considerable legal freedom to develop their own democratic practices and culture. The irony of this approach is that it is the Canadian courts, rather than the more experienced and liberal labour relations boards, that are the final legal arbiters over most internal union matters. However, this is slowly changing. Several provinces have recently enacted modest changes that direct their labour boards to hear complaints from union members respecting the fairness of internal hearings. In the absence of extensive statutory regulation, union constitutions and the democratic traditions behind them become significant legal documents. Au Canada, l’approche juridique à l’égard de la réglementation de la démocratie syndicale a consisté à chercher à mettre en équilibre les droits des membres et l’autonomie des syndicats. Les États-Unis et l’Angleterre ont une multitude de lois sur les affaires internes des syndicats, mais le Canada n’a adopté que relativement peu de lois à cet égard. Les syndicats du Canada ont joui d’une liberté juridique considérable dans l’établissement de leurs pratiques et de leur culture démocratiques. L’ironie de cette approche est que ce sont les tribunaux canadiens plutôt que les conseils des relations du travail, plus expérimentés et ayant moins de préjugés, qui sont les arbitres de dernier recours sur la plupart des questions syndicales internes. Toutefois, la situation change peu à peu. Plusieurs provinces ont adopté dernièrement de modestes modifications législatives ordonnant à leurs conseils des relations du travail d’entendre les plaintes de membres de syndicats au sujet de l’équité des audiences internes. En l’absence d’une réglementation étoffée, les statuts des syndicats et les traditions démocratiques qui les sous-tendent deviennent d’importants documents légaux.